Assessment of field oriented induction machine control strategy using new generation of inverters in BB36000 locomotive - Hamid chaikhy; Mouna Es-saadi; Mohamed Khafallah (Institute of Advanced Engineering and Science, 2022)
Due to their excellent characteristics; Reaching high voltage inverters by using lower voltage switches, reduced output current distortion, dv/dt, and switching losses decrease, efficiency rise, multilevel inverters are an interesting alternative to the two-level inverters especially in traction applications. Many studies compared both topologies, but this work compare performances of Field oriented control strategy using two levels and neutral point piloted three levels inverter supplied by space pulse width modulation. Based on real parameters, this work shows that this efficient multilevel inverter reduces current distortion and torque ripples in a manner to reduces the size and cost of all railway traction systems chosen for this work